2009
DOI: 10.1111/j.1349-7006.2008.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous T‐cell lymphoma of unspecified type with cytotoxic phenotype: Clinicopathological analysis of 27 patients

Abstract: The objective of our study was to investigate the clinicopathological features of the currently ill-defined subtype of primary cutaneous T-cell lymphoma of unspecified type (CTCLU) with a cytotoxic phenotype and no Epstein-Barr virus (EBV) association. A series of 27 patients with CTCLU (median age 49 years; range 25-87 years; 18 men) was reviewed. Performance status scores above 1 (7%), clinical stages above 2 (15%), B symptoms (26%), extracutaneous involvement (30%), and a fatal course within 1 year of diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Histologically, in most cases diffuse or nodular dense infiltrates of mostly medium to large-sized lymphocytic tumor cells with significant nuclear pleomorphism are found. 65,66 Epidermotropism is found in a subset of cases. An angiocentric component can be present.…”
Section: Cutaneous Peripheral T-cell Lymphoma Unspecifiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, in most cases diffuse or nodular dense infiltrates of mostly medium to large-sized lymphocytic tumor cells with significant nuclear pleomorphism are found. 65,66 Epidermotropism is found in a subset of cases. An angiocentric component can be present.…”
Section: Cutaneous Peripheral T-cell Lymphoma Unspecifiedmentioning
confidence: 99%
“…Variable T-cell phenotypes (CD4 1 or CD8 1 or CD4/CD8-double-negative and -double-positive) with or without expression of cytotoxic proteins are found. [66][67][68] By definition, most tumor cells do not express CD30. 1 An aberrant expression of CD20, but not additional B-cell markers, can be observed in a subset of cases.…”
Section: Cutaneous Peripheral T-cell Lymphoma Unspecifiedmentioning
confidence: 99%
“…1 Only a few/Very few case series have been documented in the literature. 2,3 Despite the rarity of these tumors, clinicians as well as dermatopathologists and pathologists should be familiar with these rare CPTLs, especially because most of these lymphomas exhibit an unfavourable prognosis. 4…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of this disease is usually poor, which can be attributed to highly aggressive clinical lesions that usually result in a rapid metastatic spread, a lower response rate to chemotherapy, and a higher incidence of relapse [77]. Conversely, some cases with a favorable outcome have been reported [78,79], suggesting that CD8TCL has a heterogeneous clinical behavior. In this regard, it was suggested that patients presenting with a single or few nonaggressive lesions and who respond well to conventional CD4?…”
Section: Primary Cutaneous CD T-cell Lymphomamentioning
confidence: 99%
“…mycosis fungoides, lymphomatoid papulosis type D, and indolent CD8? lymphoproliferation of the ear or acral sites, should be differentiated based on pathological and clinical findings [77][78][79]. The prognosis of this disease is usually poor, which can be attributed to highly aggressive clinical lesions that usually result in a rapid metastatic spread, a lower response rate to chemotherapy, and a higher incidence of relapse [77].…”
Section: Primary Cutaneous CD T-cell Lymphomamentioning
confidence: 99%